Ensuring information security in the higher education system from the perspective of classifying information assets - CHIRIAC, Liubomir; BOGDANOVA, Violeta; SVINAROVA, Hanna (Acta et Commentationes, Sciences of Education, 2023)
The article considers the threats arising in the information environment of a higher educational institution. The risks of threats to integrity, confidentiality and accessibility are assessed. In accordance with the presented categories of information assets of the higher educational institution, the necessary measures for their protection are described.